Easy! multiply the 6% by $8 then add it to the $8, now, multiply the 15% by the total of the cost with tax. then you all that to the total. ($9.75)
Answer:
Step-by-step explanation:
Each successive year, he
earned a 5% raise. It means that the salary is increasing in geometric progression. The formula for determining the nth term of a geometric progression is expressed as
Tn = ar^(n - 1)
Where
a represents the first term of the sequence(amount earned in the first year).
r represents the common ratio.
n represents the number of terms(years).
From the information given,
a = $32,000
r = 1 + 5/100 = 1.05
n = 20 years
The amount earned in his 20th year, T20 is
T20 = 32000 × 1.05^(20 - 1)
T20 = 32000 × 1.05^(19)
T20 = $80862.4
To determine the his total
earnings over the 20-year period, we would apply the formula for determining the sum of n terms, Sn of a geometric sequence which is expressed as
Sn = (ar^n - 1)/(r - 1)
Therefore, the sum of the first 20 terms, S20 is
S20 = (32000 × 1.05^(20) - 1)/1.05 - 1
S20 = (32000 × 1.653)/0.05
S20 = $1057920
The given expression is ![3b^2*(\sqrt[3]{54a}) + 3*(\sqrt[3]{2ab^6})](https://tex.z-dn.net/?f=%203b%5E2%2A%28%5Csqrt%5B3%5D%7B54a%7D%29%20%2B%203%2A%28%5Csqrt%5B3%5D%7B2ab%5E6%7D%29%20)
This can be simplified as :
= ![3*b^2*(\sqrt[3]{27 *2*a}) + 3*(\sqrt[3]{2*a*b^6})](https://tex.z-dn.net/?f=%203%2Ab%5E2%2A%28%5Csqrt%5B3%5D%7B27%20%2A2%2Aa%7D%29%20%2B%203%2A%28%5Csqrt%5B3%5D%7B2%2Aa%2Ab%5E6%7D%29%20)
We know that: ![\sqrt[3]{27} = 3](https://tex.z-dn.net/?f=%20%5Csqrt%5B3%5D%7B27%7D%20%20%3D%203%20%20%20)
Similarly we also can simplify: ![\sqrt[3]{b^6} = b^2](https://tex.z-dn.net/?f=%20%20%5Csqrt%5B3%5D%7Bb%5E6%7D%20%20%3D%20b%5E2%20)
So our expression will look like this:
= ![3*3*b^2*(\sqrt[3]{2a}) + 3*b^2*(\sqrt[3]{2a})](https://tex.z-dn.net/?f=%203%2A3%2Ab%5E2%2A%28%5Csqrt%5B3%5D%7B2a%7D%29%20%2B%203%2Ab%5E2%2A%28%5Csqrt%5B3%5D%7B2a%7D%29%20)
= ![9b^2*(\sqrt[3]{2a}) + 3b^2*(\sqrt[3]{2a})](https://tex.z-dn.net/?f=%209b%5E2%2A%28%5Csqrt%5B3%5D%7B2a%7D%29%20%2B%203b%5E2%2A%28%5Csqrt%5B3%5D%7B2a%7D%29%20)
=![\sqrt[3]{2a}*(9b^2 + 3b^2)](https://tex.z-dn.net/?f=%20%20%5Csqrt%5B3%5D%7B2a%7D%2A%289b%5E2%20%2B%203b%5E2%29%20)
=![\sqrt[3]{2a}*(12b^2)](https://tex.z-dn.net/?f=%20%5Csqrt%5B3%5D%7B2a%7D%2A%2812b%5E2%29%20)
This can also be written as:
![12b^2(\sqrt[3]{2a})](https://tex.z-dn.net/?f=%2012b%5E2%28%5Csqrt%5B3%5D%7B2a%7D%29%20)
So the Answer is Option B
Answer:
where is the question so that I can solve it
Answer:it's an equilateral triangle
Step-by-step explanation:
Can I have brainliest I'm almost upgraded